Development of Critical and Creative Skills-Based Interactive Learning Media for High School Physics Learning - Puti Zafirah Maharani Sastra; Fanny Rahmatina Rahim; Silvi Yulia Sari (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Science and technology, which continue to experience development in education at the school level, raise demands and improvements in the learning process. In the 21st century, critical and creative thinking skills are needed for students. Therefore, interactive learning media are developed to make students more active and can make improvements to students' critical and creative thinking skills. The development of interactive learning media aims to create interactive learning media based on critical and creative thinking skills on valid and practical circular motion material. This study used the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation test resulted in the developed interactive learning media obtained a result of 0.78 with a reasonably valid category. The validation results showed that the interactive learning media was not yet valid, so it needed to be revised based on the validator's suggestions to make the product more valid. After revision, the product was declared usable. The results of the practicality test conducted on high school physics teachers in Padang obtained 91% results, indicating that interactive learning media is practical to use. Based on the results of the validation test and practicality test, interactive learning media based on critical and creative thinking skills in circular motion material is declared valid and practical.